First-degree familial relationships coincidences in a population database of Jujuy (Argentina) compared with simulated populations. Issue 1 (December 2019) - Martínez, Juan José; Tula Molina, Marcos Felipe; Sánchez, Luis Adrián; Deus, María Inés; Ramella, María Isabel; Maurín, Gladys Beatriz; Martínez, Gustavo; Chernomoretz, Ariel; Escobar, María Soledad; Sibilla, Gustavo; Miozzo, María Cecilia
Abstract: Jujuy, a province from Northwestern Argentina, has a population with a great input of the Native American gene pool together with European and African contributions. For forensic purposes, a frequency population database was built by selecting 500 nonrelated individuals from Jujuy province and genotyping them with 21 autosomal STRs from the kit GlobalFiler™. The genetic profiles were incorporated in GENis (software developed in Argentina for storage and comparison of DNA profiles) to corroborate the lack of matches under high stringency. After this confirmation, we performed a searching strategy with low stringency, often used to find parent-child relationships. As a result, four (4) adventitious matches were found. One hundred (100) populations were simulated; with 500 random genetic profiles each one, using Jujuy allele frequencies. The coincidences for these populations were on average 2.07 (95% CI: 1.77–2.36) and there were no significant differences between Jujuy and the simulated populations. It is known that the number of adventitious matches increases when you go down with search stringency in DNA databases. Thus, care should be taken when searching for first-degree relationships, even with a high number of markers. LR calculations and complementary studies (such as extra autosomal markers, Y chromosome, and mitochondrial DNA) should be performed in this kind of search.